The Influence of Good Corporate Governance on the Financial Performance of Insurance Companies Listed on the Indonesia Stock Exchange for the Period 2020-2023 - Afriana, Wendra; Kurniawan, Tikkyrino; Mulatsih (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2025)
This study aims to analyze the effect of the board of directors and audit committee on the financial performance of insurance companies listed on the IDX in 2020-2023. The sampling technique that will be applied in this study is purposive sampling so as to obtain 16 companies with a total of 64 data which are then averaged into 16 data on insurance companies listed on the IDX in 2020-2023 which match the research criteria. The conclusion obtained from this research is that the board of directors affects financial performance and the audit committee affects financial performance.